3RD INTERNATIONAL FORUM "REDUCING CHILD MORTALITY - THE RUSSIAN EXPERIENCE OF UNIVERSAL PEDIATRIC CARE COVERAGE FOR CHILD POPULATION AS AN INSTRUMENT FOR ACHIEVING MILLENNIUM DEVELOPMENT GOALS" (Union of pediatricians of Russia, 2014)
.